The rise of nine - Lore, Pittacus (Penguin Books, 2013)
Until I met John Smith, Number Four, I'd been on the run alone, hiding and fighting to stay alive. Together we are much more powerful. But it could only last so long before we had to separate to find the others...I went to Spain to find Seven, and I found even more, including a tenth member of the Garde who escaped from Lorien alive. Ella is younger than the rest of us, but just as brave. Now we're looking for the others - including John. But so are they. I am Number Six. To finish what they started, they'll have to fight us first.